CONCEPTUALISATION OF CONSCIOUS LEADERSHIP - Marinčič, Dejan; Marič, Miha (International Journal of Economic Practice and Policy, 2019)
Conscious leadership is a recent construct, which we do not yet know much about. Most leaders already have their own way of management, which they often associate with their way of life. Thus, we know various ways of managing. A true conscious leader must be aware of his position and his mission, and must strive to be educated every day, work on his own consciousness, form his own context of life, try to perceive information from the surroundings, learn from life experiences, and closely monitor all the events around him. There are many ways to teach us how to become a good leader, and we ourselves need to figure out which theory and method of leadership best suits us and is most appropriate for us. In conscious leadership, we must first become self-aware; we must have a systemic insight, must be conscious of things and build on collective consciousness. Conscious guidance is a way of life that we build for years and years. A good conscious leader is the one who learns and improves daily until the end of his career and wants to leave a positive mark in the world. We will study what and how influences on the level of conscious leadership, and how we can become a good conscious leader. We will achieve this through a critical review of secondary literature and a synthesis of relevant literature in which this topic is addressed, as well as a clarified narrow scientific field of conscious leadership and the effects of conscientious leadership on followers in organisations. We will also create a conceptual model of conscious leadership.